PENGARUH KARAKTERISTIK PEKERJAAN DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA (Jurnal Mahasiswa Pasca Sarjana, 2013)
Purpose of this study is to examine and analyze the effect of job characteristics , leadership styles on performance by mediating organizational commitment and job satisfaction ( a study at the Department of Agriculture , Agriculture and Forestry and the Department of Animal Husbandry and Fisheries Waterford County ) .Total sample number of 107 people . Primary data were obtained using a questionnaire developed from the indicator variable job characteristics , leadership styles on employee performance with the mediation of organizational commitment and job satisfaction . Top scores on the questionnaire using a Likert scale of 1 to 7 continuum . Methods of data using multiple regression analysis .Job Characteristics hypothesis testing results and did not have a significant negative impact on Organizational Commitment , Leadership Style has a positive and significant impact on Organizational Commitment , Job Characteristics and did not have a significant negative effect on Job Satisfaction , Leadership Style and Organizational Commitment has a positive and significant impact on satisfaction work, employment and Characteristics of Leadership Style has a positive and significant effect on Employee Performance and Organizational Commitment and Job Satisfaction has a positive and significant influence on employee performance. Key words : Job Characteristics, Leadership Style, Organizational Commitment, Job Satisfaction and Performance